Examine the Effect of Tender Offers and Mergers Announcement on Shareholders' Wealth of Targets and Acquirers in Hong Kong - Lau, Hiu Ting (2007)
Previous research has found significant positive returns to shareholders of the target firm, but the findings on stockholder returns of acquiring firms are ambiguous. A lot more research has been done on the Mergers and Acquisitions (M&A) in the U.S. and Europe, when compared to that done on M&As in the Hong Kong context. Differences between these contexts of significance could be the economic environment, tax structure and regulatory environment which, in Hong Kong, are different from those in the US and Europe. For example, hostile acquisitions rarely take place in Hong Kong. Capital gains in Hong Kong are not subject to tax as well. The majority of mergers and tender offers employ cash as the method of payment etc. Thus it may not be suitable to apply to Hong Kong the M&A analysis developed for the US and Europe without modification.